2009
DOI: 10.1051/0004-6361/200810984
|View full text |Cite
|
Sign up to set email alerts
|

Long-slit spectrophotometry of the multiple knots of the polar ring galaxy IIZw71

Abstract: Aims. The blue compact dwarf galaxy IIZw71 is catalogued as a probable polar-ring galaxy, and along its long axis it has several very luminous knots showing recent episodes of star formation. Our main aim is to study the physical properties, the stellar content, and the kinematics in the brightest knots of the polar ring. Methods. We carried out long-slit spectroscopic observations of the polar ring in the spectral range 3500-10 000 Å taken with the William Herschel Telescope (WHT). The spectroscopic observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
5
13
1
Order By: Relevance
“…This difference is greater than the estimated observational errors and is similar (or even smaller) to what is found in other works with the spatial resolution of knots that belong to H ii galaxies or blue compact dwarf galaxies (see e.g. Izotov et al 1997; Vílchez & Iglesias‐Páramo 1998; Kehrig et al 2008; Cairós et al 2009a; Pérez‐Montero et al 2009; García‐Benito et al 2010). However, in general, these differences were attributed to the observational uncertainties (pointing errors, seeing variations, etc.)…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This difference is greater than the estimated observational errors and is similar (or even smaller) to what is found in other works with the spatial resolution of knots that belong to H ii galaxies or blue compact dwarf galaxies (see e.g. Izotov et al 1997; Vílchez & Iglesias‐Páramo 1998; Kehrig et al 2008; Cairós et al 2009a; Pérez‐Montero et al 2009; García‐Benito et al 2010). However, in general, these differences were attributed to the observational uncertainties (pointing errors, seeing variations, etc.)…”
Section: Discussionsupporting
confidence: 87%
“…8, different empirical calibrations give results that are not in complete agreement with direct measurements and the goodness of the result even changes between knots when using the same calibrator. Pérez‐Montero et al (2009) found a very similar behaviour for the star‐forming knots of IIZw71, except for the Ar 3 /O 3 parameter, which is a better estimator of the oxygen abundances for the knots in SDSS J1657. For two knots in Mrk 1418, Cairós et al (2009a) derived the oxygen abundances from the observed [O iii ] λ 4363 Å auroral emission line and compared them with those abundance values derived using the N2 and O3N2 empirical parameters, and found a similar discrepancy, with the empirically derived values being slightly larger.…”
Section: Discussionmentioning
confidence: 63%
“…From the average values of L(H α ) 2.36 × 10 36 erg/s for UGC 7576 and L(H α ) 5.33 × 10 35 erg/s for UGC 9796, we have obtained an average SFR ∼ 1.9 × 10 −5 M /yr and SFR ∼ 4.2 × 10 −6 M /yr, respectively. These values are significantly lower than those obtained for NGC 4650A (Spavone et al 2010), which is SFR ∼ 0.06 M /yr, and for IIZw71 (Pérez-Montero et al 2009), which is SFR ∼ 0.035 M /yr.…”
Section: Star Formation Ratecontrasting
confidence: 66%
“…We also compared our new results with those obtained by Pérez-Montero et al (2009) for IIZw71, a blue compact dwarf (2001), versus radius. The superimposed lines are the linear best fit derived by Pilyugin et al (2006); the red line represents the best fit to the abundance of oxygen-rich spirals, while the blue line is those related to ordinary spirals.…”
Section: Metallicity-luminosity Relationmentioning
confidence: 92%
“…This occurs when the object is very compact, or even extended but with few star‐forming knots, and when good spatial and spectral resolution together with a simultaneous wide spectral coverage are required (see e.g. Hägele et al 2006, 2007, 2008, 2009, 2010, 2011; Cumming et al 2008; Hägele 2008; López‐Sánchez & Esteban 2009b, 2010a; Pérez‐Montero et al 2009; Firpo et al 2010; Paper I; López‐Sánchez 2010; López‐Sánchez & Esteban 2010b).…”
Section: Introductionmentioning
confidence: 99%